Declarative and Procedural Knowledge: teaching of Experimental Analysis of Behavior (Brazilian Journal of Behavioral and Cognitive Therapy, 2004)
Professors who teach how to teach (Experimental Analysis of Behavior - EAB - professors, forinstance) should be the most effective professionals in the field of education. This does not seem tobe true. To become so, Teaching should be faced in a scientific way. We should look for teachingpractices that allow all professors to teach well and all students to learn as efficiently as theirrepertoires permit. EAB, a discipline that is highly dedicated to the comprehension and theteaching of learning processes, must follow its theories and procedures when the issue is thepractice of teaching. Since 1964, we have a teaching methodology that reflects, in the practice, thesetheories: PSI (Personalized System of Instruction). The present paper discuss the PSI, trying to callbehavior analysts' attention to this efficient teaching methodology, in agreement with thebehavior-analytic principlesweteach.